Changes in lung function after surgery for mesothelioma. (February 2013) - Ploenes, Till; Osei-Agyemang, Thomas; Krohn, Alexander; Waller, Cornelius F; Duncker-Rohr, Viola; Elze, Mirjam; Passlick, Bernward
Background: The effect of pleurectomy/decortication or extrapleural pleuropneumonectomy on pulmonary function has not yet been evaluated. The aim of this study was to determine the parameters of pulmonary function before and after pleurectomy/decortication or extrapleural pleuropneumonectomy. Methods: We conducted a review of 48 patients with unilateral malignant pleural mesothelioma who underwent pleurectomy/decortication or extrapleural pleuropneumonectomy. Data including medical history, histology, survival, and pre- and postoperative pulmonary function were extracted from the medical database of the University Medical Center Freiburg, or sought by telephone interview with the general practitioner or patients. Results: 25 patients underwent extrapleural pleuropneumonectomy and 23 had pleurectomy/decortication. Pulmonary function was not significantly reduced in the pleurectomy/decortication group postoperatively. In the extrapleural pleuropneumonectomy group, the median preoperative total lung capacity of 4.8 L (77.7%) differed significantly from the postoperative total lung capacity of 3.5 L (55.3%; p  < 0.0006). The median vital capacity was significantly reduced from 2.8 L (77.7%) preoperatively to 1.8 L (47.6%) postoperatively ( p  < 0.0002). Other parameters were also highly significantly reduced after extrapleural pleuropneumonectomy. Conclusions: Pleurectomy/decortication preserved good pulmonary function, whereas extrapleural pleuropneumonectomy significantly reduced pulmonary function, which may lead to dyspnea and influence the quality of life of these patients.